Determination of the relationship between the moisture content and microwave dielectric properties in kenaf stem - Radzuan, Mohd Nazren; Abdan, Khalina; Ismail, Alyani; Janius, Rimfiel (Faculty of Engineering, Universiti Putra Malaysia, 2012)
A brief history of kenaf stem moisture content measurement by sensing the dielectric properties of kenaf stem is presented. The basic principles are also described for using microwave dielectric properties of kenaf stem for sensing moisture through their correlation with moisture content. Development of these techniques will provide useful instruments for on-line monitoring of moisture content in kenaf stem processing to separate between bast and core of kenaf stem and thus increase the quality of natural fibre, prevent spoilage in storage and transport, improve processing, and provide information important for yield determinations in precision agriculture applications.